Nonlinear response and reliability analysis of tunnels under strong earthquakes. Issue 5 (3rd May 2016) - Yue, Qingxia; Ang, Alfred H.-S.
Abstract : The damages of tunnels under earthquakes showed that soil–rock deposits around a tunnel have significant effects on its response to earthquake excitations, caused by the spatial variability and correlation of the soil properties, which may properly be modelled as a random field. This paper studied these effects through modelling the surrounding soil as a random field on the response of a tunnel and made some comparisons with the corresponding deterministic analysis. A two-dimensional finite element model of the tunnel-soil system was examined, and the corresponding random field was simulated by the spectral representation method. The results revealed that the corners of the tunnel are the critical locations for the axial force and bending moment. The comparisons showed that the results of the deterministic analysis usually yield higher results than the corresponding random field results. The reliabilities of a tunnel for two limit-state functions were considered: one is defined as exceeding the design limit according to the Chinese design code, whereas the other is exceeding the ultimate strength of the reinforced concrete tunnel lining. The equivalent extreme events were formulated for the respective limit-state functions, from which the tunnel system reliability can be evaluated. The probability density evolution method was used to calculate the stochastic response and reliability of the tunnel under a strong earthquake.